2009
DOI: 10.1080/07853890802502614
|View full text |Cite
|
Sign up to set email alerts
|

Can misfolded proteins be beneficial? The HAMLET case

Abstract: By changing the three-dimensional structure, a protein can attain new functions, distinct from those of the native protein. Amyloid-forming proteins are one example, in which conformational change may lead to fibril formation and, in many cases, neurodegenerative disease. We have proposed that partial unfolding provides a mechanism to generate new and useful functional variants from a given polypeptide chain. Here we present HAMLET (Human Alpha-lactalbumin Made LEthal to Tumor cells) as an example where partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 104 publications
2
40
0
1
Order By: Relevance
“…Such mutant formed a tumoricidal HAMLET-like complex with OA, but the partially unfolded protein alone did not kill tumor cells. Another non-native -lactalbumin variant with all amino acids building disulfide bridges substituted by Ala residues also did not exhibit cytotoxic activity in the absence of OA, while its HAMLET-like form displayed strong tumoricidal activity against lymphoma and carcinoma cell lines [13]. Together, these experiments consistently confirmed that both molten globule like protein conformation and specific fatty acids are required for the tumoricidal activity of the investigated complexes.…”
Section: Origin Of Hamlet -Human α-Lactalbumin Made Lethal For Tumor supporting
confidence: 73%
“…Such mutant formed a tumoricidal HAMLET-like complex with OA, but the partially unfolded protein alone did not kill tumor cells. Another non-native -lactalbumin variant with all amino acids building disulfide bridges substituted by Ala residues also did not exhibit cytotoxic activity in the absence of OA, while its HAMLET-like form displayed strong tumoricidal activity against lymphoma and carcinoma cell lines [13]. Together, these experiments consistently confirmed that both molten globule like protein conformation and specific fatty acids are required for the tumoricidal activity of the investigated complexes.…”
Section: Origin Of Hamlet -Human α-Lactalbumin Made Lethal For Tumor supporting
confidence: 73%
“…Hence, unlike amyloid fibril examples, deliberately engineered, nonnative, partially unfolded structural ensembles may surprisingly confer cytotoxic effects selectively to tumor cells or, in other words, independent beneficial effects to the host cells. 40 In light of the 100% authentic population of the molten globule state with rHLA all-Ala and rHLA all-Ala -OA, we are able to speculate the nature of the small native-like population contained within HAMLET. In other words, does HAMLET partition into fatty acid-bound molten globule molecules and fatty-acid-free native molecules, or are the molecules exhibiting native-like signatures (CD and NMR; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…While it is becoming evident that biological activity can be maintained even after partial unfolding of a protein 38 and a considerable proportion of eukaryotic proteins are known to possess biological activity in their unstructured states, 39 the example of α-lactalbumin and HAMLET shows that a protein can exhibit significantly distinct biological functions depending on whether it is in the native or partially unfolded state. 40 In this paper, we provide insight into how the lack of native threedimensional structure in the α-lactalbumin protein positively contributes to the selective in vivo tumoricidal activity of the complex.…”
mentioning
confidence: 99%
“…Sixty different types of amyloid protein have been identified so far, and thirty-six have been connected with deposition disease. 7,8 For example, AA amyloidosis is caused by the deposition of an acute phase reactant protein in various organs. This acute phase reactant is usually generated in the setting of inflammatory disease (inflammatory bowel disease, rheumatoid arthritis, etc) or chronic infection (tuberculosis, chronic osteomyelitis, etc).…”
Section: Discussionmentioning
confidence: 99%